Analysis of SMKK Costs in the Ngantang Sub-District Office Renovation Project Based on Minister of PUPR Regulation No. 10 of 2021 - Lakshita Umanis Fauzi; Tri Kuncoro; Mei Fajri Anugrah Sukma; Retno Dwi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to evaluate the appropriateness of the Construction Safety Management System (SMKK) cost allocation in the Ngantang Sub-District Office Renovation Project, Malang Regency, against the provisions of Minister of PUPR Regulation No. 10 of 2021. The research method used is descriptive quantitative with a desk study approach to analyze the Engineer's Estimate (EE) documents of the project valued at IDR 199.732.000.00. Risk analysis results indicate the presence of "High" to "Extreme" hazard categories, particularly the risks of workers not using personal protective equipment (PPE), being struck by materials, and work areas not separated from public activities. Although the SMKK budget allocation of IDR 1.974.715.38 has been provided, the evaluation found that several components such as Work Protective Equipment (APK), PPE specifications, and the qualifications of OHS personnel are still not in compliance with regulatory standards and the risk levels of renovation work. This study recommends budget adjustments for technical protection items and competent supervision to ensure the effectiveness of risk control in the field.